2016
DOI: 10.1002/jor.23174
|View full text |Cite
|
Sign up to set email alerts
|

Knee and ankle biomechanics with lateral wedges with and without a custom arch support in those with medial knee osteoarthritis and flat feet

Abstract: Rather than prescribing lateral wedges to all patients with knee osteoarthritis, those who have medial knee osteoarthritis and flat feet may prefer to use the combined orthotic to reduce loads across the knee, and to minimize the risk of foot and ankle symptoms as a consequence of orthotic treatment. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1597-1605, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 36 publications
1
38
1
1
Order By: Relevance
“…For the purposes of the meta-analysis, unlike the KAM, the magnitudes of the ankle/subtalar eversion angle and moment were deemed to be relatively consistent between 20% and 80% of stance,16 and data were pooled from studies reporting overall peaks, mean values and values at the time of early and late stance KAM peaks (figure 3). In general, LWIs produce small-to-medium increases in ankle/subtalar eversion angles (SMD=−0.48, 95% CI: −0.91 to –0.06, I 2 =77%, p=0.03) and subsequently large increases in external ankle eversion moments (SMD=−0.84, 95% CI: −1.41 to –0.27, I 2 =77%, p=0.0003), however, large heterogeneity in each variable reduces the strength of the evidence.…”
Section: Resultsmentioning
confidence: 99%
“…For the purposes of the meta-analysis, unlike the KAM, the magnitudes of the ankle/subtalar eversion angle and moment were deemed to be relatively consistent between 20% and 80% of stance,16 and data were pooled from studies reporting overall peaks, mean values and values at the time of early and late stance KAM peaks (figure 3). In general, LWIs produce small-to-medium increases in ankle/subtalar eversion angles (SMD=−0.48, 95% CI: −0.91 to –0.06, I 2 =77%, p=0.03) and subsequently large increases in external ankle eversion moments (SMD=−0.84, 95% CI: −1.41 to –0.27, I 2 =77%, p=0.0003), however, large heterogeneity in each variable reduces the strength of the evidence.…”
Section: Resultsmentioning
confidence: 99%
“…[49] The inclination angles of insoles ranged from 3 degrees [43] to 11 degrees [37] and the most common angle was 5 degrees. [21,44,46,52] With regard to the medial arch support, 5 used a custom design based on patient comfort, [16,21,23,42,43] and 3 studies used prefabricated arch supports. [37,45,52] The remaining study did not report these data.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have tested the effect on EKAM of adding an arch support to the LWI during gait but showed inconsistent findings. [21,23,29,3746] Some authors found a reduction in the EKAM during the stance phase of gait using a lateral wedge and an arch support. [21,3942,4446] However, in some patients, no reductions [23,28] or smaller reductions [46] on the EKAM were observed.…”
Section: Introductionmentioning
confidence: 99%
“…The study was approved by the Institution’s Clinical Research Ethics Board and all participants provided written informed consent. In contrast to information provided on the trials registry (Clinicaltrials.gov identifier: NCT02234895), gait biomechanics data were only collected at the initial baseline data collection session, rather than at all time points, and are presented elsewhere [24]. …”
Section: Methodsmentioning
confidence: 99%